2010
DOI: 10.5194/bg-7-1469-2010
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic composition of dissolved inorganic nitrogen in high mountain lakes: variation with altitude in the Pyrenees

Abstract: Abstract. Nitrogen deposition in remote areas has increased, but the effect on ecosystems is still poorly understood. For aquatic systems, knowledge of the main processes driving the observed variation is limited, as is knowledge of how changes in nitrogen supply affect lake biogeochemical and food web processes. Differences in dissolved inorganic nitrogen (DIN) between lakes cannot be understood without considering catchment characteristics. In mountains, catchment features (e.g., thermal conditions, land cov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…4b, f). Bartrons et al (2010) have suggested that vegetated soils can contribute to high d 15 N, and the difference in catchment characteristics and morphologies between the two lakes here (Fig. Catchment soils are the largest storage pool for N, although nutrient uptake by terrestrial vegetation is also important (Fenn et al, 1998).…”
Section: Catchment and Lake Morphology Effectsmentioning
confidence: 78%
“…4b, f). Bartrons et al (2010) have suggested that vegetated soils can contribute to high d 15 N, and the difference in catchment characteristics and morphologies between the two lakes here (Fig. Catchment soils are the largest storage pool for N, although nutrient uptake by terrestrial vegetation is also important (Fenn et al, 1998).…”
Section: Catchment and Lake Morphology Effectsmentioning
confidence: 78%
“…The concentrations of NH + 4 were not sufficient for isotope measurements in the water column, except at the bottom where we found that δ 15 N values of NH + 4 averaged +3.8 ± 0.1 ‰. δ 15 N NH 4 values in the water column found in high mountain lakes in the Pyrenees ranged from −9.4 to +7.4 ‰, depending on snow-pack melting or soil conditions (Bartrons et al, 2010). On the other hand, the 2 ± 1.6 ‰ in sediment pore waters were found to be uniform, with no variations corresponding to catchment or lake characteristics, and similar to values found in our study at the bottom of the water column.…”
Section: Nitrogen Isotope Biogeochemistry In the Water Columnmentioning
confidence: 87%
“…Atmospheric deposition is the dominant source of N compounds in most high mountain and oligotrophic lakes (Ostrom et al, 1997;Wookey et al, 2009;Vreča and Muri, 2010). In addition, in high mountain lakes, another N source can be snow-pack melting influenced by soil conditions (Bartrons et al, 2010). More anthropogenic nitrate loading derived from fertilizers, manure and/or sewage can be observed in lakes located in urban areas (Townsend-Small et al, 2009).…”
Section: A Bratkic Et Al: Semi-annual Carbon and Nitrogen Isotope Vmentioning
confidence: 99%
“…This increases the local supply of N that occurs during spring thaw, resulting in a temporal mismatch between availability and biological uptake, thereby enhancing availability for leaching into surface waters during snow melt. However, Bartrons et al () showed how soil type in a catchment contributes to higher δ 15 N than that related to snow melt processes, which may reflect local soil dynamics and vegetation effects. Increased decomposition rates associated with warming and/or vegetation changes are also reflected in higher δ 15 N in soil organic matter and consequently in NO3 leached from soils to lakes, which may be recorded in lake sediments.…”
Section: Discussionmentioning
confidence: 99%